Structural analysis of Gd2Ce2O7. Issue 1743 (20th February 2015) - Patel, Maulik K.; Baldinozzi, Gianguido; Aguiar, Jeffery A.; Valdez, James A.; Vogel, Sven C.; Sickafus, Kurt E.
ABSTRACT: A complex cerium bearing oxide, Gd2 Ce2 O7 was synthesized in order to simulate Pu in a fluorite derivative oxide. X-ray diffraction (XRD) data was collected using a lab diffractometer at room temperature and analyzed by Rietveld refinement method using the xnd program. The diffraction pattern obtained from the material could be indexed as a C-type cubic bixbyite crystal structure however several peaks showed peak broadening and could not be accounted for within the single-phase bixbyite model. A full pattern refinement, assuming a possible existence of short order disordered bixbyite regions within an average disordered fluorite phase gave a good fit with the experimental data, providing an estimate for correlation length of those bixbyite regions. Transmission electron microscopy confirms the existence of these correlated domains of disordered bixbyite type phase inside a defect fluorite lattice. Understanding the extent of these domains as a function of composition and the thermal history of the samples may have a profound effect on our understanding of miscibility gaps in Re2 O3 -CeO2 phase diagrams. These effects could be eventually exploited to design materials with increased radiation resistance, a desired feature for oxide matrices where actinides can be safely disposed.